Adipose microenvironment promotes hypersialylation of ovarian cancer cells - Fox, Alexandra; Leonard, Garry D.; Adzibolosu, Nicholas; Wong, Terrence; Tedja, Roslyn; Sharma, Sapna; Gogoi, Radhika; Morris, Robert; Mor, Gil; Fehl, Charlie; Alvero, Ayesha B. (Frontiers in Oncology, 2024)
Sialylation, the addition of negatively charged sialic acid sugars to terminal ends of glycans, is upregulated in most cancers. Hypersialylation supports multiple pro-tumor mechanisms such as enhanced migration and invasion, resistance to apoptosis and immune evasion. A current gap in knowledge is the lack of understanding on how the tumor microenvironment regulates cancer cell sialylation. The adipose niche is a main component of most peritoneal cancers' microenvironment. This includes ovarian cancer (OC), which causes most deaths from all gynecologic cancers. In this report, we demonstrate that the adipose microenvironment is a critical regulator of OC cell sialylation.In vitro adipose conditioning led to an increase in both ⍺2,3 and ⍺2,6-linked cell surface sialic acids in both human and mouse models of OC. Adipose-induced sialylation reprogramming was also observed in vivo from intra-peritoneal OC tumors seeded in the adipose-rich omentum. Mechanistically, we observed upregulation of at least three sialylatransferases, ST3GAL1, ST6GAL1 and ST3GALNAC3. Hypersialylated OC cells consistently formed intra-peritoneal tumors in both immune-competent mice and immune-compromised athymic nude mice. In contrast, hyposiaylated OC cells persistently formed tumors only in athymic nude mice demonstrating that sialylation impacts OC tumor formation in an immune dependent manner. To our knowledge, this is the first demonstration of the effect of adipose microenvironment on OC tumor sialylation. Our results set the stage for translational applications targeting sialic acid pathways in OC and other peritoneal cancer tumorigenesis and metastasis.